Prognostic Value and Risk Continuum of Noninvasive Fractional Flow Reserve Derived from Coronary CT Angiography - Ihdayhid, Addul Rahman; Norgaard, Bjarne L.; Gaur, Sara; Leipsic, Jonathan; Nerlekar, Nitesh; Osawa, Kazuhiro; Miyoshi, Toru; Jensen, Jeper M.; Kimura, Takeshi; Shiomi, Hiroki; Erglis, Andrejs; Jegere, Sande; et al. (Radiology, 2019)
Background: Coronary CT angiography with noninvasive fractional flow reserve (FFR) predicts lesion-specific ischemia when compared with invasive FFR. The longer term prognostic value of CT-derived FFR (FFRCT) is unknown.
CRIS-Team WoS Importer:2019-08-02